New contexts, new processes, new strategies: the co-construction of meaning in plurilingual interactions - Capucho, Filomena (2016)
Intercomprehension (IC) canbe defined as the process of co-constructing meaning in intercultural/interlinguistic contexts.The latest developments of this notion locate the communicative processes in the context of plurilingual interactions, both in writtenhybrid forms of communication at distance (chats and forums) and in face-to-face oral conversations (cf. ARAÚJO E SÁ; DE CARLO;MELO-PFEIFER, 2011; BALBONI, 2010, among others). Further research in Applied Linguistics is required so as to support the emergent pedagogical practices aimed at developing the competences of individuals who are now seen simultaneously as IC learners and IC immediate users. This research should be grounded on a multidimensional analysis model of authentic corpora of oral plurilingual interactions in order to provide the analyst with a list of communication strategies and a detailed description of interactional processes that will allow IC specialists to assess the results of actual learning in the context of IC projects and to structure IC learning activities.In this paper, we will present the analysis of an extract from the Bucharest-Cinco corpus that will allow us to identify the strategies developed in the process of co-construction of meaning in multilingual contexts through a close examination of verbal and non-verbal features.